-10-9(x+9)=

Simple and best practice solution for -10-9(x+9)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10-9(x+9)= equation:


Simplifying
-10 + -9(x + 9) = 0

Reorder the terms:
-10 + -9(9 + x) = 0
-10 + (9 * -9 + x * -9) = 0
-10 + (-81 + -9x) = 0

Combine like terms: -10 + -81 = -91
-91 + -9x = 0

Solving
-91 + -9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '91' to each side of the equation.
-91 + 91 + -9x = 0 + 91

Combine like terms: -91 + 91 = 0
0 + -9x = 0 + 91
-9x = 0 + 91

Combine like terms: 0 + 91 = 91
-9x = 91

Divide each side by '-9'.
x = -10.11111111

Simplifying
x = -10.11111111

See similar equations:

| 3x^2-1x-30=30 | | 10x-3=35x-2 | | 6y+7x=1 | | 2x+40=x+73 | | 2=1+n/9 | | [x+7]=3x-5 | | 1=9-8r | | 360=x+72+60+78 | | 4=8+n/2 | | 1+5(8+5n)= | | -3+9(b-10)= | | 9e*7f= | | -6(4+4k)=4 | | 2(x-12)=100 | | 70*0.07+x=0.049(x+70) | | y=-200+-6(-16) | | -5+8(v-6)= | | 2x^2-26x+69=0 | | .67x+.3x=17 | | 52a+12a= | | 360=85+80+100+x | | 173-5x=6x-91 | | .7*2+x=.9(x+2) | | 9(-6-n)= | | -8=-8p+4+9p | | -2+4r=22 | | -4x+2=5x+50 | | 45+12= | | A=y+b | | 97=6-7b | | -4x+3=5x+50 | | -16x^2+4=0 |

Equations solver categories